SEPARATION OF WARINGIN HEAVY MINERAL SANDS FROM CENTRAL KALIMANTAN - NURYADI SALEH; PRAMUSANTO PRAMUSANTO (Indonesian Mining Journal, 2012)
Central Kalimantan has grown rapidly as a heavy mineral producer. Zircon is the main mineral concentrate, but other valuable heavy minerals are present. With particular interest in the upgrading of zircon and its recovery, tekMIRA’s laboratory has developed benefi ciation steps of heavy minerals to produce marketable zircon con- centrate. Using a series of concentration equipments that includes spiral concentrator, shaking table, magnetic separator and electrostatic separator; the content of zircon in the end concentrate reaches up to 65% ZrO2.